Evaluation of growth and meat performance of Pangasianodon hypopthalmus which fed with Cinnamomum burmanni leaves enriched diet - Mia Setiawati; Aliyah Sakinah; Dedi Jusadi (Jurnal Akuakultur Indonesia)
ABSTRACT